Experimental studies of the effect of ultrasonic irradiation on internal concentration polarization during forward osmosis - Hoon, Yong Yee. (2011)
Forward osmosis (FO) is one of the membrane technologies of increasingly importance. Concentration polarization phenomenon exists as a critical problem limiting the application of the membrane separation processes with high performance. Dynamic agitation has been proved to be an effective way in controlling the polarization during filtration processes. However, most of the conventional approaches are not applicable to the polarization process within the porous structure of the membrane, which is viewed as the internal concentration polarization (ICP). This paper proposes a novel approach to minimizing the internal concentration polarization by exploiting ultrasonic irradiation. Preliminary experimental studies were carried out to validate the effect of the ultrasound on the forward osmosis efficiency. A lab-scale FO testing system was designed with novel features for improving the measurement accuracy. A double layer membrane composed of a commercial FO membrane and an ultra filtration membrane was employed to simulate the case having severe ICP. The irradiation power input was varied from 0 to 80 percent at a frequency of 53 kHz. It was observed that the forward osmosis efficiency was significantly increased with increasing ultrasound power input. The presented experimental studies will provide a basis for developing the system for mitigating the ICP during FO processes with low energy consumption.